Propuesta de viabilidad de un servicio de Cloud Computing académico orientado a la Carrera de Ingeniería de Sistemas de la Universidad Politécnica Salesiana sede Quito, Campus Sur - Orbea Bautista, Byron Javier (2017)
The following analysis aims to solve the need for the implementation of a Career-Oriented Academic Cloud Computing Service in Systems Engineering at the Polytechnic Salesian Headquarters Quito, south campus, for which students and teachers were surveyed in order to observe their appreciation and knowledge about this type of service. Proposals were analyzed with updated infrastructure and could be used with the components currently owned by the career and also with new infrastructure available in the market. It will be evidenced according to the tabulation of the survey realized that the service model that students and teachers prefer and the model of deployment would be Private Cloud, as well as the subjects they would like to be in the Cloud to perform their tasks. After the analysis of costs, software and hardware that could be used, a pilot will be carried out to see the functionality of the tool with which the Cloud would be performed, for which it will work with students of Seventh level of the race, who will test of consumption of services and will record the initial and final consumptions of this test.